Juridical Analysis Of Sharp Weapon Abuse (Case Study Of Medan District Court Decision No. 2277/Pid.B / 2023 / PN Mdn) - Sitompul, Ariman; Winarko, Bagus (Universitas Dharmawangsa, 2025)
Imprisonment as a form of sanction for violations of the law, including the use of sharp weapons (sajam), is a complex issue in the context of law enforcement and social rehabilitation. This study aims to explore the impact of prison sentences on offenders involved in sajam use cases, as well as to understand how experiences in prison can contribute to learning from mistakes and behavior change in the future. The research method used is normative juridical research by conducting research systematically legal norms . The results showed that prison sentences often serve not only as a deterrent to crime, but also as a means of rehabilitation that can help offenders realize the consequences of their actions. However, many offenders feel that the punishment does not provide enough deterrent effect, especially if it is not balanced with an effective rehabilitation program. Prevention efforts need to be done through strict law enforcement, public awareness campaigns, and regulating access to sharp weapons in order to reduce crime rates and create a safer environment.